The Role and Effectiveness of the MBP Installation in Poland Based on Selected Examples - Wiśniewska, Marta; Lelicińska-Serafin, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents examples of installations for the mechanical and biological treatment of municipal waste in Poland. Each of the presented installations is defined as a regional municipal waste treatment installation (RIPOK). Their technological solutions and work efficiency have been compared in this study. In addition, the loss of waste mass as a result of processes occurring in the biological part of individual installations was calculated in the research.
Keywords: treatment of waste; biological treatment; mechanical treatment; municipal waste; mass loss; przetwarzanie odpadów; przetwarzanie biologiczne; przetwarzanie mechaniczne; odpady komunalne; utrata masy